(untitled) (Research, Society and Development, 2021)
In Brazil, until 2018, there were, in an accumulated number, 926,742 people living with HIV / AIDS (PLHIV). Antiretrovirals (ARV’s) are able to control the virus and improve the quality of life of these individuals, however, the use of these drugs can lead to the development of metabolic syndrome (MS). It is known that physical activities are protective factors for MS in healthy people, however, in patients undergoing treatment for ARVs, this association is still unclear. Objective: to identify whether physical activity is a protective factor for MS in (PLHIV) using ARVs. Method: cross-sectional, quantitative study with 265 (PLHIV) and undergoing treatment with ARVs in the specialized assistance service (SAE) of Ponta Grossa-PR between March / 2018 and May / 2019. The level of physical activity was measured using the IPAQ short version questionnaire. The data were analyzed descriptively and the association between MS and physical activity was measured with OR (odds ratio) and chi-square. Results: the average age was 43 years, 56.2% were male, 61.9% white, 71.3% heterosexual, 44.5% with elementary education, 41.1% with income of 1-2 minimum wages, 40.4% married and in 74.7% the mode of transmission was sexual. As for physical activity, 57.0% were active or irregularly active and 67.5% did not have MS. Among the active, 31.1% had MS and among the inactive 34.2%, which did not represent a statistically significant association (OR 0.87; 95% CI 0.52 - 1.46; p = 0.595). Conclusion: From this perspective, physical activity was not a protective factor for MS in (PLHIV) using antiretroviral therapies (ARV).